An Analysis of Grammatical Error on Students’ Writing - Syaiful Islam; Putri Nuril Mufidah (International Journal of English Education and Linguistics (IJoEEL), 2022)
The research was aimed to analyze the most common grammatical error on students’ writing. All categories of grammatical error types were classified and described based on Dulay on theory of Linguistic Category. The data source of this study was 26 students of the second grade of Nurul Jadid Islamic Senior High School (MANJ). In this study, observation, writing test, and documentation were used to collect data. The major findings of this study found 155 errors in the students’ writing composition. The omission error percentage is 44%. Meanwhile, addition error occurs in 27% errors, and the misformation error is 23%. The last, the misordering error is 6%. The result of the analysis shows that omission error is the most common error produced by the students. As a whole, students still committed errors in their writing. Teachers have to pay high attention to the problematic area of the grammar structure, so some pedagogical implications on the error analysis are suggested.